Self-Confidence Representation Analysis in The Album Alassia Cara Know-It-All - Luthfiansyah Luthfiansyah; Mildan Arsdan Fidinillah (Scope : Journal of English Language Teaching, 2023)
The purpose of the study is to analyze the representation of self-confidence in the song lyrics in the album Alessia Cara Know-It-All by using the denotative meaning and connotative meaning in Roland Barthes' Semiotics and Lindenfield’s theory. In this research, the writers used Semiotic theory put forward by Roland Barthes which divides Semiotics into three parts, namely denotative meaning, connotative meaning and myth as well as to represent self-confidence, the writers used Lindenfield's theory which states that there are four characteristics of self-confidence, namely: (1) Self-love, (2) Self-understanding, (3) Clear goals, and (4) Positive mind. In the three parts of Roland Barthes' Semiotics, the discussion is limited by representing self-confidence through denotative and connotative meanings according to the data the writer found in the album Alessia Cara Know-It-All. Based on the results of the analysis, the representation of self-confidence in the Know-It-All album is 30 data altogether consisting of self-love 2 data or 6.7%, self-understanding is 5 data or 16.7%, clear goals is 13 data or 43.3% and being positive is 10 data or 33.3%. So it can be concluded that the most dominant representation is a clear goal.